Dual-dimension carbon-coated silicon-carbon negative electrode material and preparation method and application thereof

By using dual-dimensional carbon coating technology in silicon-carbon anode materials, using metal nanoparticle catalysts to deposit elemental nanosilicon at high temperatures, and forming a coated structure of one-dimensional carbon fiber and two-dimensional graphene-based carbon layer, the problem of poor cyclic stability of silicon-carbon anode materials is solved, and higher conductivity and better charge and discharge performance are achieved.

CN119560532APending Publication Date: 2025-03-04XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411740537.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing silicon carbon anode materials have problems such as poor cycling stability, low ionic conductivity and electronic conductivity during charging and discharging, which cannot meet the application needs of fast charging and rapid discharge of lithium-ion batteries.

Method used

A silicon-carbon negative electrode material with dual dimension carbon coating was designed and synthesized, and the metal nanoparticles were pre-embedded in the carbon material matrix particles, and the elemental nanosilicon was deposited at high temperature under a catalyst, and formed under double coating of carbon fiber and graphene-like carbon layers.

Benefits of technology

The cycle life and capacity retention rate of silicon-carbon anode material are improved, the charging and discharging performance in lithium-ion batteries is enhanced, and the ionic conductivity and electronic conductivity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560532A_ABST
    Figure CN119560532A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery materials, and particularly relates to a dual-dimensional carbon-coated silicon-carbon negative electrode material as well as a preparation method and application thereof. The silicon-carbon negative electrode material comprises silicon-carbon composite particles, the silicon-carbon composite particles comprise carbon material matrix particles and elemental nano silicon attached to the carbon material matrix particles; the carbon material matrix particles contain metal nanoparticles; the surfaces of the carbon material matrix particles are coated with one-dimensional carbon fibers, and the surface of the elemental nano silicon is coated with a two-dimensional graphene-like carbon layer. The preparation method is characterized in that the metal nanoparticles are pre-embedded in the carbon material matrix particles to induce and regulate the generation of a specific carbon structure, and meanwhile, the ionic conductivity and the electronic conductivity of the silicon-carbon negative electrode material are improved, so that the cycle performance and the capacity retention ratio of the silicon-carbon negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery materials, and specifically relates to a silicon-carbon negative electrode material with double-dimensional carbon coating, and a preparation method and application thereof. Background Art

[0002] Silicon-based negative electrode materials have a low lithium extraction / insertion potential and can provide a higher energy density. At the same time, their working potential is slightly higher than the lithiation potential of graphite, which can largely avoid lithium precipitation. They are considered to be a promising new generation of lithium-ion battery negative electrode materials. However, due to the huge volume expansion problem caused by the alloying reaction of silicon and lithium during the charging and discharging process, the material is easy to peel off and pulverize, affecting the material's cycle stability; at the same time, silicon, as a traditional semiconductor material, has low ionic conductivity and electronic conductivity, resulting in poor lithium ion diffusion kinetics. Therefore, when silicon is actually used as the active material of the negative electrode in lithium-ion batteries, elemental silicon is usually combined with a carbon skeleton to make silicon-carbon composite particles as silicon-carbon negative electrode materials. Although this material synthesis idea has improved the conductivity problem of silicon to a certain extent, the currently synthesized silicon-carbon negative electrode materials still have large volume changes during the charging and discharging process and low ionic and electronic conductivity, which still cannot meet the current application requirements of fast charging and discharging of lithium-ion batteries as power sources for many electronic products. In addition, due to the side reaction between the elemental silicon exposed on the surface of the particles and the battery electrolyte, such silicon-carbon composite materials cannot work stably in the battery. Summary of the invention

[0003] The purpose of the present invention is to provide a silicon-carbon negative electrode material with double-dimensional carbon coating and its preparation method and application in view of the shortcoming that the silicon-carbon negative electrode material prepared by the prior art has poor cycle stability.

[0004] After extensive and profound research, the inventors of the present invention have found that in silicon-carbon negative electrode materials, only silicon atomic sites have true electrochemical lithium storage activity, that is, only silicon can undergo Faraday reactions with lithium ions to achieve stable chemical bonding and charge transfer of lithium ions; carbon atomic sites in silicon-carbon negative electrode materials can usually only play non-Faraday reaction roles such as electron transmission, stabilizing material structure, and catalyzing the formation of electrolyte interface layers. In theory, the design of carbon layer coating should be able to perform specific structural regulation of silicon atomic sites and carbon atomic sites respectively for their functions, while improving the ionic conductivity and electronic conductivity of silicon-carbon negative electrode materials, thereby improving the cycle life and capacity retention rate of silicon-carbon negative electrode materials. However, the carbon coating technology currently used in the industry for silicon-carbon negative electrode materials can only obtain a uniform and indifferent carbon coating structure, and cannot effectively improve the active sites of the material kinetically, that is, it cannot improve the ionic conductivity and electronic conductivity at the same time. Although the implementation method of indifferent carbon coating of silicon-carbon particles is simple, it cannot most effectively bring into play the role of different atomic sites in electrochemical reactions, and the differentiated carbon coating design for different atomic sites is often complex and difficult to achieve.

[0005] On this basis, the inventors of the present invention have designed and synthesized a silicon-carbon negative electrode material with dual-dimensional carbon coating, by in-situ embedding metal ions in carbon material matrix particles, and then pre-embedding metal nanoparticle catalysts on carbon material matrix particles through reduction reaction, using silicon source gas to undergo chemical cracking reaction at high temperature, depositing elemental nanosilicon on carbon material matrix particles, and obtaining silicon-carbon composite particles, and then introducing hydrocarbon encapsulation gas at high temperature. Under the catalytic action of high temperature and metal nanoparticles, hydrocarbon gas is cracked into carbon atoms and other small molecules on the particle surface, and carbon atoms are subsequently dissolved in metal nanoparticles to form carbon-containing metal carbides or carbon dissolved in metal. When the carbon in the metal nanoparticles reaches an oversaturated state, carbon atoms begin to precipitate from specific crystal planes of the metal nanoparticles to form carbon filaments. These carbon filaments grow in a specific direction (usually perpendicular to the surface of the matrix) under the guidance of the metal particles to form a one-dimensional carbon fiber structure. While the carbon atom sites of the silicon-carbon composite particles are induced and regulated by metal nanoparticle catalysts and a one-dimensional carbon fiber structure grows vertically on the particle surface, a two-dimensional graphene-like carbon layer film is generated along the particle surface at the silicon atom sites of the silicon-carbon composite particles, thereby realizing the preparation of a silicon-carbon negative electrode material with a dual-dimensional carbon coating structure. Based on this, the present invention is completed.

[0006] In the first aspect, the present invention provides a silicon-carbon negative electrode material with dual-dimensional carbon coating, wherein the silicon-carbon negative electrode material comprises silicon-carbon composite particles; the silicon-carbon composite particles comprise carbon material matrix particles and elemental nano-silicon attached to the carbon material matrix particles; the carbon material matrix particles contain metal nano-particles; the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers, and the surface of the elemental nano-silicon is coated with a two-dimensional graphene-like carbon layer.

[0007] In a preferred embodiment, the median particle size D50 of the silicon-carbon composite particles is 3 to 20 μm.

[0008] In a preferred embodiment, the mass ratio of elemental nano-silicon to carbon material matrix particles in the silicon-carbon composite particles is (0.2-1.7):1.

[0009] In a preferred embodiment, the average length of the carbon fibers is 0.1 to 2000 nm.

[0010] In a preferred embodiment, the average diameter of the carbon fibers is 0.1-100 nm.

[0011] In a preferred embodiment, the thickness of the graphene-like carbon layer is 0.1-20 nm.

[0012] In a preferred embodiment, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.01-20 wt %.

[0013] In a preferred embodiment, the particle size of the metal nanoparticles is 0.1 to 10 nm.

[0014] In a preferred embodiment, the metal nanoparticles contain at least one element selected from iron, cobalt, nickel, manganese, titanium, copper, zinc, vanadium, chromium, zirconium and molybdenum.

[0015] In a preferred embodiment, the metal nanoparticles are single metal nanoparticles and / or alloy metal nanoparticles.

[0016] In a second aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material having a dual-dimensional carbon coating, the method for preparing the silicon-carbon negative electrode material comprising the following steps:

[0017] S1. After mixing the carbon-based raw material with the metal precursor, the obtained carbon precursor material is subjected to a first heat treatment to obtain carbon material matrix particles, wherein the carbon material matrix particles contain one of metal ions, metal oxides, and metal nano-single substances;

[0018] S2. The carbon material matrix particles obtained in step S1 are subjected to a third heat treatment in the presence of a silicon-containing gas to obtain silicon-carbon composite particles, wherein the silicon-carbon composite particles include carbon material matrix particles and elemental nano-silicon, and the carbon material matrix particles contain one of metal ions, metal oxides, and metal nano-element;

[0019] S31. The silicon-carbon composite particles obtained in step S2 are first subjected to a reduction treatment in an activated gas atmosphere to convert metal ions or metal oxides in the carbon material matrix particles into metal nanoparticles, thereby obtaining silicon-carbon composite particles containing metal nanoparticles. Subsequently, the silicon-carbon composite particles are subjected to a coating treatment in an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with a one-dimensional carbon fiber and the surface of the single nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material having a dual-dimensional carbon coating;

[0020] Alternatively, S32. The silicon-carbon composite particles containing metal nano-elements obtained in step S2 are coated in an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with one-dimensional carbon fibers and the surface of the elemental nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material with a double-dimensional carbon coating.

[0021] In a preferred embodiment, in step S1, the mass ratio of the carbon-based raw material to the metal precursor is 1:(0.02-0.1).

[0022] In a preferred embodiment, the conditions of the first heat treatment include: a temperature of 600-800° C. and a time of 0.5-2 h.

[0023] In a preferred embodiment, the carbon-based raw material is selected from at least one of phenolic resin, epoxy resin, polyaniline, petroleum coke, and liquid asphalt.

[0024] In a preferred embodiment, the metal precursor is selected from at least one of transition metal nanoparticles, transition metal oxides, transition metal halides, transition metal sulfates, transition metal nitrates, and transition metal phosphates.

[0025] In a preferred embodiment, the carbon material matrix particles also include a second heat treatment in the presence of an alkaline substance before the third heat treatment to obtain carbon material matrix particles containing metal ions having a porous structure, wherein the porous carbon matrix particles contain one of metal ions, metal oxides, and metal nano-elements.

[0026] In a preferred embodiment, the mass ratio of the carbon material matrix particles to the alkaline substance is 1:(0.2-0.8).

[0027] In a preferred embodiment, the conditions of the second heat treatment include: a temperature of 700 to 900° C. and a time of 0.5 to 2 hours.

[0028] In a preferred embodiment, the alkaline substance is selected from at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate and sodium bicarbonate.

[0029] In a preferred embodiment, in step S2, the ratio of silane gas to inert gas I in the silicon-containing gas is (0.05-0.25):1.

[0030] In a preferred embodiment, the flow rate of the silicon-containing gas is 14-16 L / min relative to 1000 g of the carbon material matrix particles.

[0031] In a preferred embodiment, the conditions of the third heat treatment include: a temperature of 500-600° C. and a time of 1-3 hours.

[0032] In a preferred embodiment, in step S3, the ratio of reducing gas to inert gas II in the activation gas is (0.1-0.5):1.

[0033] In a preferred embodiment, the reducing gas is hydrogen or carbon monoxide.

[0034] In a preferred embodiment, the ratio of the carbon source gas to the inert gas III in the encapsulating gas is (0.3-1):1.

[0035] In a preferred embodiment, the carbon source gas is selected from at least one of methane, ethane, propane, acetylene, propyne, ethylene and propylene.

[0036] In a preferred embodiment, the flow rate of the encapsulating gas is 4-6 L / min relative to 5000 g of the silicon-carbon composite particles containing metal ions.

[0037] In a preferred embodiment, the reduction treatment conditions include: a temperature of 200 to 600° C. and a time of 1 to 3 hours.

[0038] In a preferred embodiment, the coating treatment conditions include: a temperature of 600 to 900° C. and a time of 1 to 3 hours.

[0039] In a third aspect, the present invention also provides a silicon-carbon negative electrode material with double-dimensional carbon coating prepared by the above method.

[0040] In a fourth aspect, the present invention also provides the use of the above-mentioned silicon-carbon negative electrode material with double-dimensional carbon coating in lithium-ion batteries.

[0041] The key to the present invention is to design and synthesize a silicon-carbon negative electrode material with dual-dimensional carbon coating. Metal nanoparticles are pre-embedded in carbon material matrix particles to induce and regulate the formation of a specific carbon structure, and a one-dimensional carbon fiber structure is coated on the surface of the carbon material matrix particles (carbon atom sites). A two-dimensional graphene-like carbon layer structure is coated on the surface of elemental nanosilicon (silicon atom sites). The preparation of a silicon-carbon negative electrode material with dual-dimensional carbon coating is achieved, which can simultaneously improve the ionic conductivity and electronic conductivity of the silicon-carbon negative electrode material, thereby improving the cycle performance and charge and discharge performance (first coulomb efficiency and first charge and discharge reversible specific capacity) of the silicon-carbon negative electrode material. The reasons are speculated to be: (1) The one-dimensional carbon fiber structure effectively improves the electronic conductivity of the silicon-carbon negative electrode material. The one-dimensional carbon fiber structure coated on the surface of the carbon material matrix particles can effectively connect the carbon material matrix particles and the elemental nano-silicon particles to construct a stable and continuous conductive network, providing more electron transmission channels and reducing the transmission distance of electrons between silicon particles, thereby improving the electronic conductivity of the silicon-carbon negative electrode material, which is beneficial to improving its charge and discharge performance in battery applications, improving capacity retention and cycle performance; (2) The one-dimensional carbon fiber structure effectively slows down the damage to the electrode caused by the volume expansion of the silicon-carbon material, thereby improving the cycle life of the silicon-carbon negative electrode material in battery applications. The conductive network formed by the carbon fiber has a structural support skeleton function. Its large specific surface area and excellent elasticity can absorb the volume change of silicon to a certain extent, relieve the stress of the volume change of the silicon-carbon particles during the charge and discharge process, and reduce the silicon-carbon negative electrode in The collapse of the particle structure during the lithium ion insertion and extraction process maintains the integrity of the electrode structure, thereby improving the cycle performance. In addition, the one-dimensional carbon fiber structure on the surface of the silicon-carbon negative electrode particles can also connect the electrode material particles together, improve the connection strength between the particles and the electrode adhesion, reduce the shedding of active substances, effectively improve the expansion and pulverization problem of the silicon-carbon negative electrode, and improve the cycle performance; (3) The two-dimensional graphene-like carbon layer film coated on the silicon atom site can effectively improve the ion conduction rate of the material on the one hand. Since the ion transition barrier in the normal direction of the graphene-like carbon layer is much smaller than that of the ordinary carbon layer, that is, lithium ions can more easily pass through the graphene-like carbon layer to enter the silicon site, which is beneficial to improve the charge and discharge performance and cycle performance of the silicon-carbon negative electrode material. On the other hand, the two-dimensional graphene-like carbon layer film also helps to form a stable solid electrolyte interface (SEI) film to protect the electrode from the erosion of the electrolyte and lithium ions and extend the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the structure of the silicon-carbon negative electrode material with double-dimensional carbon coating prepared in Example 1.

[0043] Figure 2 This is a SEM image of the silicon-carbon negative electrode material with double-dimensional carbon coating prepared in Example 1. DETAILED DESCRIPTION

[0044] The silicon-carbon negative electrode material with dual-dimensional carbon coating provided by the present invention includes silicon-carbon composite particles; the silicon-carbon composite particles include carbon material matrix particles and simple nano-silicon attached to the carbon material matrix particles; the carbon material matrix particles contain metal nano-particles; the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers, and the surface of the simple nano-silicon is coated with a two-dimensional graphene-like carbon layer. The metal nano-particles are preferably dispersed on the surface of the carbon material matrix particles. The simple nano-silicon is attached to the surface of the carbon material matrix particles and / or in the pore structure. The morphology of the carbon material matrix particles can be at least one of spherical, elliptical, cylindrical, flaky, blocky or other morphologies.

[0045] In the present invention, the median particle size D50 of the silicon-carbon composite particles is preferably 3 to 20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or any value therebetween. The mass ratio of elemental nano-silicon to carbon material matrix particles in the silicon-carbon composite particles is preferably (0.2 to 1.7):1, such as 0.2:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.7:1 or any value therebetween.

[0046] In the present invention, the average length of the carbon fiber is preferably 0.1 to 2000 nm, such as 0.1 nm, 0.5 nm, 1 nm, 10 nm, 20 nm, 50 nm, 80 nm, 100 nm, 300 nm, 500 nm, 1000 nm, 1500 nm, 2000 nm or any value therebetween, which is more conducive to forming an interlaced conductive network and forming connections between particles, thereby improving the overall conductivity and stability of the silicon-carbon negative electrode material and giving it ideal cycle performance. The average diameter of the carbon fiber is preferably 0.1 to 100 nm, such as 0.1 nm, 0.5 nm, 1 nm, 5 nm, 10 nm, 25 nm, 50 nm, 80 nm, 100 nm or any value therebetween, which is more conducive to forming an interlaced conductive network and further improving the conductive properties of the silicon-carbon negative electrode material. The thickness of the graphene-like carbon layer is preferably 0.1 to 20 nm, such as 0.1 nm, 0.5 nm, 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm or any value therebetween. Controlling the thickness of the graphene-like carbon layer within the above preferred range is more conducive to further reducing the transition barrier of lithium ions and improving the lithium ion transmission efficiency, thereby improving the charge and discharge performance and cycle performance of the silicon-carbon negative electrode material.

[0047] In the present invention, the content of metal nanoparticles in the silicon-carbon negative electrode material is preferably 0.01-20wt%, such as 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 5wt%, 8wt%, 10wt%, 15wt%, 20wt% or any value therebetween. Controlling the content of metal nanoparticles within the above preferred range is more conducive to the stable growth of the one-dimensional carbon fiber structure, ensuring its uniform distribution and high consistency of length and diameter. The particle size of the metal nanoparticles is preferably 0.1-10nm, such as 0.1nm, 0.5nm, 1nm, 2nm, 5nm, 8nm, 10nm or any value therebetween, which is more conducive to the growth of one-dimensional carbon fibers with smaller diameter, good morphology and uniformity, and improving the electrical conductivity and cycle performance of the material. The elements contained in the metal nanoparticles are preferably at least one of iron, cobalt, nickel, manganese, titanium, copper, zinc, vanadium, chromium, zirconium and molybdenum. The metal nanoparticles are preferably single metal nanoparticles and / or alloy metal nanoparticles.

[0048] The method for preparing the silicon-carbon negative electrode material with dual-dimensional carbon coating provided by the present invention comprises the following steps:

[0049] S1. After mixing the carbon-based raw material with the metal precursor, the obtained carbon precursor material is subjected to a first heat treatment to obtain carbon material matrix particles, wherein the carbon material matrix particles contain one of metal ions, metal oxides, and metal nano-single substances;

[0050] S2. The carbon material matrix particles obtained in step S1 are subjected to a third heat treatment in the presence of a silicon-containing gas to obtain silicon-carbon composite particles, wherein the silicon-carbon composite particles include carbon material matrix particles and elemental nano-silicon, and the carbon material matrix particles contain one of metal ions, metal oxides, and metal nano-element;

[0051] S31. The silicon-carbon composite particles obtained in step S2 are first subjected to a reduction treatment in an activated gas atmosphere to convert metal ions or metal oxides in the carbon material matrix particles into metal nanoparticles, thereby obtaining silicon-carbon composite particles containing metal nanoparticles. Subsequently, the silicon-carbon composite particles are subjected to a coating treatment in an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with a one-dimensional carbon fiber and the surface of the single nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material having a dual-dimensional carbon coating;

[0052] Alternatively, S32. The silicon-carbon composite particles containing metal nano-elements obtained in step S2 are coated in an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with one-dimensional carbon fibers and the surface of the elemental nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material with a double-dimensional carbon coating.

[0053] In the present invention, in step S1, the mass ratio of the carbon-based raw material to the metal precursor is preferably 1: (0.02-0.1), such as 1: 0.02, 1: 0.05, 1: 0.08, 1: 0.1 or any value therebetween. The conditions of the first heat treatment may include: the temperature is preferably 600-800°C, such as 600°C, 650°C, 700°C, 750°C, 800°C or any value therebetween; the time is preferably 0.5-2h, such as 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h or any value therebetween. The first heat treatment is preferably carried out under an inert gas atmosphere.

[0054] In the present invention, in step S1, the mixing method of the carbon-based raw material and the metal precursor can be dry mixing or wet mixing, preferably wet mixing. The wet mixing preferably combines one of metal ions, metal oxides, and metal nano-singles to the carbon-based raw material based on the impregnation principle, and the specific steps are as follows: After the carbon-based raw material is mixed and stirred with the metal precursor and water for 10 to 14 hours, a carbon precursor material containing metal ions, metal oxides, or metal nano-singles is obtained by spray drying or solvent evaporation. After the first heat treatment, it also includes coarse breaking, crushing, and sieving the obtained carbon material to obtain carbon material matrix particles with a specific particle size. The median particle size D50 of the carbon material matrix particles is preferably 3 to 20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or any value therebetween.

[0055] In the present invention, the carbon-based raw material can be a precursor raw material conventionally used to prepare carbon materials in the prior art, preferably at least one of phenolic resin, epoxy resin, polyaniline, petroleum coke, and liquid asphalt. The metal precursor is preferably at least one of transition metal nano-element, transition metal oxide, transition metal halide, transition metal sulfate, transition metal nitrate, and transition metal phosphate. The transition metal is preferably at least one of iron, cobalt, nickel, manganese, titanium, copper, zinc, vanadium, chromium, zirconium, and molybdenum.

[0056] In the present invention, the carbon material matrix particles preferably further include a second heat treatment in the presence of an alkaline substance before the third heat treatment to obtain a carbon material matrix particle having a porous structure, wherein the porous carbon matrix particle contains one of metal ions, metal oxides, and metal nano-single substances. The mass ratio of the carbon material matrix particles to the alkaline substance is preferably 1: (0.2-0.8), such as 1: 0.2, 1: 0.3, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8 or any value therebetween. The conditions for the second heat treatment may include: the temperature is preferably 700-900°C, such as 700°C, 750°C, 800°C, 850°C, 900°C or any value therebetween; the time is preferably 0.5-2h, such as 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h or any value therebetween. The second heat treatment is preferably carried out under an inert gas atmosphere. The alkaline substance is preferably at least one selected from potassium hydroxide, sodium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate and sodium bicarbonate.

[0057] In the present invention, the carbon material matrix particles and the alkaline substance are preferably mixed by dry mixing. The second heat treatment may also include washing and drying treatment: washing the product obtained by the second heat treatment with water until the washing liquid is neutral, and drying to obtain the carbon material matrix particles with a porous structure.

[0058] In the present invention, in step S2, the ratio of silane gas to inert gas I in the silicon-containing gas is preferably (0.05-0.25):1, such as 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1 or any value therebetween. Relative to 1000g of the carbon material matrix particles, the flow rate of the silicon-containing gas is preferably 14-16L / min, such as 14L / min, 14.5L / min, 15L / min, 15.5L / min, 16L / min or any value therebetween, which is more conducive to the uniform distribution of elemental nano-silicon in the carbon material matrix particles. The conditions of the third heat treatment may include: the temperature is preferably 500-600°C, such as 500°C, 520°C, 550°C, 580°C, 600°C or any value therebetween; the time is preferably 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween. The silane gas is preferably at least one selected from monosilane, disilane and chlorosilane.

[0059] In the present invention, in step S31, the ratio of the reducing gas to the inert gas II in the activated gas is preferably (0.1-0.5):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or any value therebetween. The reducing gas is preferably hydrogen or carbon monoxide. The ratio of the carbon source gas to the inert gas III in the encapsulating gas is preferably (0.3-1):1, such as 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1:1 or any value therebetween, which is more conducive to uniform spatial distribution of the gas in the reactor and controllable deposition rate. The carbon source gas is preferably at least one of methane, ethane, propane, acetylene, propyne, ethylene and propylene. The inert gas I and the inert gas II can be conventional choices in the art, and each is independently preferably nitrogen and / or argon.

[0060] In the present invention, in step S31 and step S32, relative to 1000g of the silicon-carbon composite particles, the flow rate of the encapsulating gas is preferably 4-6L / min, such as 4L / min, 4.5L / min, 5L / min, 5.5L / min, 6L / min or any value therebetween, which is more conducive to controlling the active collision between the gas and the surface of the material, controlling the reaction rate, and reducing the generation of by-products. The conditions for the reduction treatment may include: the temperature is preferably 200-600°C, such as 200°C, 300°C, 400°C, 500°C, 600°C or any value therebetween; the time is preferably 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween. Controlling the temperature of the reduction treatment within the above preferred range is more conducive to the complete reduction reaction and the generation of metal nanoparticles with a small particle size and uniformly distributed on the carbon material matrix particles, thereby facilitating the subsequent formation of one-dimensional carbon fibers with good morphology. The coating treatment conditions may include: the temperature is preferably 600-900°C, such as 600°C, 700°C, 750°C, 800°C, 850°C, 900°C or any value therebetween; the time is preferably 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween. Controlling the coating treatment temperature within the above preferred range is more conducive to controlling the gas deposition efficiency and forming a stable coating layer structure.

[0061] In the present invention, in step S32, since the metal nano-substance may also be oxidized during the previous preparation process, the silicon-carbon composite particles containing the metal nano-substance obtained in step S2 may also be reduced in an activated gas atmosphere before being coated. The method and conditions of the reduction treatment may refer to the reduction treatment in step S31.

[0062] In addition, the term "D50 particle size" means the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. The terms "first", "second", "third", "Ⅰ", "Ⅱ", and "Ⅲ" are used for descriptive purposes only and cannot be understood as limiting the number or type of technical features or indicating or suggesting their importance.

[0063] The present invention will be described in detail below through specific embodiments.

[0064] Example 1

[0065] S1. Phenolic resin, deionized water and Ni(NO3)2 are prepared in a mass ratio of 9.5:90:0.5, and the agitator is stirred at a speed of 300 rpm for 12 hours until the materials are evenly dispersed to obtain a mixed solution L1 and spray-dried to obtain a carbon precursor powder F1 containing nickel element. The carbon precursor powder F1 containing nickel element is then heated in a nitrogen atmosphere furnace with a nitrogen flow rate of 200 mL / min and a holding temperature of 700°C for a holding time of 1 hour. The obtained product is coarsely broken, pulverized and sieved to obtain a carbon powder F2 containing nickel element with a median particle size D50 of 6 μm.

[0066] S2. Weigh the carbon powder F2 containing nickel element and the activator KOH in a mass ratio of 1:0.5, mix them in a mixer and place them in a nitrogen atmosphere furnace for heating. The activation temperature is 800°C and the activation time is 1 hour. The obtained product is repeatedly ultrasonically washed and filtered until the washing liquid is neutral. After drying, a porous carbon material matrix particle powder F3 containing nickel element is obtained.

[0067] S3. Place 1000g of porous carbon material matrix particle powder F3 containing nickel element in a fluidized bed reactor, heat it up in a nitrogen atmosphere with a nitrogen flow rate of 13L / min, introduce silane gas (specifically monosilane) after heating to 520°C and keep warm for 2h with a silane gas flow rate of 2L / min. Nitrogen is continuously introduced during the entire heating and insulation process to obtain silicon-carbon composite particle powder F5 containing nickel element, wherein the mass ratio of elemental nano-silicon and porous carbon material matrix particles is 1:1.

[0068] S4. Place 1000g of silicon-carbon composite particle powder F5 containing nickel element in a rotary kiln reactor, heat it up in a nitrogen atmosphere with a nitrogen flow rate of 3L / min, introduce hydrogen when the temperature reaches 400℃ with a hydrogen flow rate of 1L / min, keep warm for 2h, turn off the hydrogen, continue to heat it to 600℃, introduce acetylene gas and keep warm for 2h with an acetylene flow rate of 2L / min, and continue to introduce nitrogen during the whole heating and insulation process to obtain a silicon-carbon negative electrode material with double-dimensional carbon coating, wherein the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers and the surface of the single nano-silicon is coated with a two-dimensional graphene-like carbon layer, the median particle size D50 is 8μm, the thickness of the graphene-like carbon layer is 2nm, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.16wt% and the particle size is 5nm.

[0069] Depend on Figure 1 and Figure 2 It can be seen that the circle box represents the location of the elemental nano-silicon, and its surface is smooth, indicating that the graphene-like carbon layer is coated on the surface of the elemental nano-silicon, and the carbon fiber structure is coated on the surface of the carbon material matrix particles, indicating the successful preparation of dual-dimensional carbon-coated silicon-carbon negative electrode materials.

[0070] Example 2

[0071] A silicon-carbon negative electrode material with a dual-dimensional carbon coating is prepared according to the method of Example 1, except that in step S1, the same mass of Fe(NO3)3 is used instead of Ni(NO3)2, and the mass ratio of phenolic resin to deionized water and Ni(NO3)2 is 9.7:90:0.3, and in step S3, the temperature when hydrogen is introduced is 500°C, the temperature when ethylene is introduced is 650°C, the ethylene gas flow rate is 1 L / min, and the other conditions are the same as in Example 1, thereby preparing a silicon-carbon negative electrode material with a dual-dimensional carbon coating, wherein one-dimensional carbon fibers are coated on the surface of carbon material matrix particles, two-dimensional graphene-like films are coated on the surface of elemental nano-silicon, the median particle size D50 is 8 μm, the thickness of the graphene-like carbon layer is 2 nm, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.07wt%, and the particle size is 5 nm.

[0072] Example 3

[0073] A silicon-carbon negative electrode material with a dual-dimensional carbon coating is prepared according to the method of Example 1, except that the same mass of Co(NO3)2 is used instead of Ni(NO3)2, and the mass ratio of phenolic resin to deionized water and Ni(NO3)2 is 9.3:90:0.7. The temperature when hydrogen is introduced in step S3 is 300°C, the temperature when ethane gas is introduced is 700°C, the ethane gas flow rate is 2.5 L / min, and the remaining conditions are the same as in Example 1. Thus, a silicon-carbon negative electrode material with a dual-dimensional carbon coating is prepared, wherein one-dimensional carbon fibers are coated on the surface of carbon material matrix particles, two-dimensional graphene-like films are coated on the surface of elemental nano-silicon, the median particle size D50 is 8 μm, the thickness of the graphene-like carbon layer is 2 nm, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.22 wt%, and the particle size is 5 nm.

[0074] Example 4

[0075] A silicon-carbon negative electrode material with a dual-dimensional carbon coating is prepared according to the method of Example 1, except that step S2 is not performed, and the other conditions are the same as those of Example 1, thereby preparing a silicon-carbon negative electrode material with a dual-dimensional carbon coating, wherein the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers and the surface of the elemental nano-silicon is coated with a two-dimensional graphene-like carbon layer, the median particle size D50 is 8 μm, the thickness of the graphene-like carbon layer is 2 nm, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.16 wt%, and the particle size is 5 nm.

[0076] Example 5

[0077] A silicon-carbon negative electrode material with a dual-dimensional carbon coating is prepared according to the method of Example 1, except that the temperature when hydrogen is introduced in step S3 is 800°C, thereby preparing a silicon-carbon negative electrode material with a dual-dimensional carbon coating, wherein the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers and the surface of the elemental nano-silicon is coated with a two-dimensional graphene-like carbon layer, the median particle size D50 is 8μm, the thickness of the graphene-like carbon layer is 2nm, the content of metal nanoparticles in the silicon-carbon negative electrode material is 0.16wt%, and the particle size is 20nm.

[0078] Comparative Example 1

[0079] A reference silicon-carbon negative electrode material was prepared according to the method of Example 1, except that Ni(NO3)2 was not added in step S1, and the other conditions were the same as those of Example 1, thereby preparing a reference silicon-carbon negative electrode material.

[0080] Comparative Example 2

[0081] A reference silicon-carbon negative electrode material was prepared according to the method of Example 1, except that hydrogen was not introduced in step S1, and the other conditions were the same as those of Example 1, thereby preparing a reference silicon-carbon negative electrode material.

[0082] Test Case

[0083] The silicon-carbon negative electrode materials prepared in the above examples and comparative examples were tested for the first charge / discharge specific capacity, the first coulombic efficiency and the cycle capacity retention rate according to the following method. The results are shown in Table 1.

[0084] (1) Assembly method of button half-cell: The prepared silicon-carbon negative electrode material is mixed with the conductive agent and the binder in a mass ratio of silicon-carbon negative electrode material: conductive agent: binder = 93:2:5, and then a solvent is added to make a pole piece slurry with a solid content of 40wt%. The slurry is applied on the copper foil with a scraper, and then placed in an oven at 80°C for drying to prepare the battery pole piece and cut it into a circular pole piece with a diameter of 14mm. The prepared circular pole piece, diaphragm, electrolyte, lithium sheet, gasket, and spring are placed in the button battery CR2032 plastic shell in sequence, and then covered with a steel shell, and the button battery is pressed under a pressure of 50Kg to obtain a button half-cell.

[0085] (2) Test of first discharge specific capacity, first charge specific capacity and first coulombic efficiency: After the button half-cell assembled according to the method in (1) was placed at 25°C for 8 hours, it was charged at a constant current of 0.1C to a cut-off voltage of 1.5V, and the charge capacity was recorded; it was discharged at a constant current of 0.1C to 0.01V, and then deeply discharged at 0.01C to 0.005V, and the discharge capacity was recorded, from which the first charge specific capacity, first discharge specific capacity and first coulombic efficiency can be calculated. Among them, the first coulombic efficiency = first discharge specific capacity / first charge specific capacity × 100%.

[0086] (3) Cycle capacity retention rate test: The button half-cell assembled according to the method in (1) was tested on a battery testing system (LANDCT2001A tester). The charge and discharge cycles were carried out at a constant current of 1C in the voltage range of 0.005 to 1.5V under room temperature conditions. The discharge capacities at the cycle numbers of 100, 200, 300, 400, and 500 were recorded in turn, and the cycle capacity retention rate was calculated.

[0087] Table 1

[0088]

[0089]

[0090] It can be seen from the results in Table 1 that compared with Comparative Examples 1 and 2, the silicon-carbon negative electrode material with dual-dimensional carbon coating provided by the embodiment of the present invention has good cycle stability. After 500 cycles at a rate of 1C, the capacity retention rate is still maintained above 90%, and the capacity decrease rate is significantly lower than that of the comparative example. At the same time, it also has a higher first coulombic efficiency and first charge / discharge specific capacity.

[0091] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A silicon-carbon negative electrode material with dual-dimensional carbon coating, characterized in that: The silicon-carbon negative electrode material includes silicon-carbon composite particles; the silicon-carbon composite particles include carbon material matrix particles and elemental nano-silicon attached to the carbon material matrix particles; the carbon material matrix particles contain metal nano-particles; the surface of the carbon material matrix particles is coated with one-dimensional carbon fibers, and the surface of the elemental nano-silicon is coated with a two-dimensional graphene-like carbon layer.

2. The silicon-carbon negative electrode material with dual-dimensional carbon coating according to claim 1, characterized in that: The median particle size D50 of the silicon-carbon composite particles is 3 to 20 μm; preferably, the mass ratio of elemental nano-silicon to carbon material matrix particles in the silicon-carbon composite particles is (0.2 to 1.7):

1.

3. The silicon-carbon negative electrode material with dual-dimensional carbon coating according to claim 1, characterized in that: The average length of the carbon fibers is 0.1 to 2000 nm; preferably, the average diameter of the carbon fibers is 0.1 to 100 nm; preferably, the thickness of the graphene-like carbon layer is 0.1 to 20 nm.

4. The silicon-carbon negative electrode material with dual-dimensional carbon coating according to claim 1, characterized in that: The content of metal nanoparticles in the silicon-carbon negative electrode material is 0.01 to 20 wt%; preferably, the particle size of the metal nanoparticles is 0.1 to 10 nm; preferably, the elements contained in the metal nanoparticles are selected from at least one of iron, cobalt, nickel, manganese, titanium, copper, zinc, vanadium, chromium, zirconium, and molybdenum; preferably, the metal nanoparticles are elemental metal nanoparticles and / or alloy metal nanoparticles.

5. A method for preparing a silicon-carbon negative electrode material with a dual-dimensional carbon coating, characterized in that: The preparation method of the silicon-carbon negative electrode material comprises the following steps: S1. After mixing the carbon-based raw material with the metal precursor, the resulting carbon precursor material is subjected to a first heat treatment to obtain carbon material matrix particles, wherein the carbon material matrix particles contain one of metal ions, metal oxides, and metal nanoparticles; S2. The carbon material matrix particles obtained in step S1 are subjected to a third heat treatment in the presence of a silicon-containing gas to obtain silicon-carbon composite particles, wherein the silicon-carbon composite particles include carbon material matrix particles and elemental nano-silicon, and the carbon material matrix particles contain one of metal ions, metal oxides, and metal nano-element; S31. The silicon-carbon composite particles obtained in step S2 are first subjected to a reduction treatment in an activating gas atmosphere to convert metal ions or metal oxides in the carbon material matrix particles into metal nanoparticles, thereby obtaining silicon-carbon composite particles containing metal nanoparticles. Subsequently, a coating treatment is performed in an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with one-dimensional carbon fibers and the surface of the elemental nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material having a dual-dimensional carbon coating; Alternatively, S32. The silicon-carbon composite particles containing metal nano-elements obtained in step S2 are coated under an encapsulating gas atmosphere to coat the surface of the carbon material matrix particles with one-dimensional carbon fibers and the surface of the elemental nano-silicon with a two-dimensional graphene-like carbon layer, thereby obtaining a silicon-carbon negative electrode material with a double-dimensional carbon coating.

6. The method for preparing a silicon-carbon negative electrode material having a dual-dimensional carbon coating according to claim 5, characterized in that: In step S1, the mass ratio of the carbon-based raw material to the metal precursor is 1:(0.02-0.1); Preferably, the conditions of the first heat treatment include: temperature of 600-800°C and time of 0.5-2h; Preferably, the carbon-based raw material is selected from at least one of phenolic resin, epoxy resin, polyaniline, petroleum coke, and liquid asphalt; Preferably, the metal precursor is selected from at least one of transition metal nanoparticles, transition metal oxides, transition metal halides, transition metal sulfates, transition metal nitrates, and transition metal phosphates.

7. The method for preparing a silicon-carbon negative electrode material having a dual-dimensional carbon coating according to claim 5, characterized in that: The carbon material matrix particles are further subjected to a second heat treatment in the presence of an alkaline substance before the third heat treatment to obtain carbon material matrix particles having a porous structure, wherein the porous carbon matrix particles contain one of metal ions, metal oxides, and metal nanoparticles; Preferably, the mass ratio of the carbon material matrix particles to the alkaline substance is 1:(0.2-0.8); Preferably, the conditions of the second heat treatment include: temperature of 700-900°C and time of 0.5-2h; Preferably, the alkaline substance is selected from at least one of potassium hydroxide, sodium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and sodium bicarbonate.

8. The method for preparing a silicon-carbon negative electrode material having a dual-dimensional carbon coating according to claim 5, characterized in that: In step S2, the ratio of silane gas to inert gas I in the silicon-containing gas is (0.05-0.25):1; Preferably, the flow rate of the silicon-containing gas is 14 to 16 L / min relative to 1000 g of the carbon material matrix particles; Preferably, the conditions of the third heat treatment include: a temperature of 500-600° C. and a time of 1-3 hours.

9. The method for preparing a silicon-carbon negative electrode material having a dual-dimensional carbon coating according to claim 5, characterized in that: In step S3, the ratio of reducing gas to inert gas II in the activation gas is (0.1-0.5):1; Preferably, the reducing gas is hydrogen or carbon monoxide; Preferably, the ratio of the carbon source gas to the inert gas III in the encapsulating gas is (0.3-1):1; Preferably, the carbon source gas is selected from at least one of methane, ethane, propane, acetylene, propyne, ethylene, and propylene; Preferably, the flow rate of the encapsulating gas is 4 to 6 L / min relative to 1000 g of the silicon-carbon composite particles; Preferably, the reduction treatment conditions include: temperature of 200-600°C, time of 1-3h; Preferably, the coating treatment conditions include: temperature of 600-900° C. and time of 1-3 hours.

10. A silicon-carbon negative electrode material with dual-dimensional carbon coating prepared by the method according to any one of claims 5 to 9.

11. Use of the silicon-carbon negative electrode material with dual-dimensional carbon coating according to any one of claims 1 to 4 or claim 10 in a lithium-ion battery.

Citation Information

Cited By

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN120637442A